Investment Strategies In Malaysian Shariah-compliant Equities With Transaction Costs - Siti Masitah Elias; Karmila Hanim Kamil; Muhammad Zaim Razak (Universiti Sains Islam Malaysia, 2024)
Shariah compliant equity is a type of security that is permissible in Islam for investment purposes. Classification of Shariah compliant equity includes the process of screening firm’s nature of business and investment activities that are free from the element of riba, gharar and maysir. In Islamic perspective, risk management is highly encouraged. Therefore, investors are expected to accumulate wealth responsibly by applying risk management measures in their investments. In this study, 50 equities have been selected from stocks listed in FBM EMAS KLCI from January 2009 until June 2011. This study intends to enlighten investors in term of constructing optimal portfolio of diversified Shariah compliant equities in Malaysian market by applying Markowitz portfolio selection model. The aim of the model is to maximize portfolio’s return by specifying investor’s tolerable level of risk. Furthermore, this study extended the model with regards to transaction costs in measuring cost effectiveness of portfolio rebalancing. This study will benefit investors in selecting portfolio of Shariah compliant equities which are not only optimal but also cost effective. Results from the study shows that by applying Markowitz model, investor can achieve higher return at fixed level of tolerable risk as compared to naïve investment strategy. While the benefits of portfolio rebalancing outweigh the disadvantage when transaction cost is taken into consideration during portfolio rebalancing. The performance of portfolio by applying Markowitz model outperforms the FBM EMAS KLCI index. With this knowledge, Shariah compliant investors are capable to invest responsibly in managing their wealth. By applying risk management measure, Shariah compliant investor will become more confident investing in Shariah compliant equity portfolio to safeguard and accumulate wealth.